TRANSACTIONAL COSTS OF RATIONAL NUTRITION: COMPARING NEOCLASSICAL AND INSTITUTIONAL APPROACHES - Yu. V. Dubrovskaya; R. I. Chupin (Russian Journal of Economics and Law)
The article attempts to economically interpret the new and poorly researched object – rational nutrition. Comparing various theoretical approaches to these issues revealed the excellence of institutional paradigm, according to which the inappropriate nutrition of individuals is caused by high transactional costs. It is proved that taking these factors into account will ensure making effective decisions in building the rational nutrition of population, and, consequently, promotion of such topical issue as the country’s food security.